AN EMPIRICAL STUDY ON JOB SATISFACTION OF THE EMPLOYEES OF PRIVATE SCHOOLS AND COLLEGES IN BILASPUR DIVISION OF CHHATTISGARH - Jyotsna, Tanya; Gupta, Umesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Job satisfaction is a crucial determinant of the productivity and morale of employees, especially in the education sector, which is responsible for nation-building. This study investigates the level of job satisfaction among employees of private schools and colleges in the Bilaspur division of Chhattisgarh. Using both primary and secondary data, this empirical research explores factors influencing job satisfaction, such as salary, work environment, leadership, career advancement opportunities, and work-life balance. A structured questionnaire was administered to 300 respondents selected through stratified random sampling from private educational institutions across Bilaspur, Ratanpur, Pendra, and Kawardha. The study employs descriptive statistics, Chi-square tests, and regression analysis to draw meaningful inferences. The results indicate moderate satisfaction levels, with salary and job security emerging as major concerns. The paper offers actionable suggestions for institutional management and policymakers to improve job satisfaction and reduce attrition in private education.